Phytochemistry and Antibacterial Assessment of Ethyl acetate Leaf Extract of Newbouldia laevis - Bello, A.B; Suleiman, A; Idris, A.D (UMYU Journal of Microbiology Research)
A current trend in drug research is the desire to obtain novel antimicrobials with plant origins as an alternative therapy and a means to curb antimicrobial resistance. This study evaluated the phytochemistry and antibacterial activity of ethyl acetate leaf extract of Newbouldia laevis. The leaf of Newbouldia laevis was cold extracted with Ethyl acetate. The extract was evaluated for it phytochemical constituents using standard methods and antibacterial effect against some clinical bacterial isolates using well diffusion technique. The study revealed the presence of some phytochemicals, alkaloids, saponins, flavonoids, phenol, anthraquinones and steroids in the plant extract, which were believed to be a contributing factor to the observed antibacterial effects. The test isolates' susceptibility to the crude extract was measured at 25 mg/mL and 50 mg/mL, 75mg/mL and 100mg/mL. The growth inhibition of Escherichia coli, Salmonella typhi, Klebsiella pneumoniae, Staphylococcus aureus and Pseudomonas aeruginosa ranges from 9.66±1.54 to 13.00±0.00, 10.00±1.00 to 11.00±1.00, 9.33±0.57 to 11.00±1.00, 14.00±0.00 to 17.33±1.52 and 9.33±0.57 to 10.66± 1.52 mm respectively. The Minimum Inhibitory Concentration was observed at 25mg/mL, 12.5mg/mL, 25mg/mL,12.5mg/mL and 25mg/mL against Escherichia coli, Salmonella typhi, Klebsiella pneumoniae, Staphylococcus aureus and Pseudomonas aeruginosa respectively while the Minimum Bactericidal Concentrations was at 50mg/mL, 25mg/mL, 50mg/mL, 25mg/mL and 50mg/mL respectively. The observed antibacterial effects were believed to be due to the presence of alkaloids, saponins, flavonoids, phenol, anthraquinones and steroids detected in the extract. The results apparently justified the traditional use of this plant in treating bacterial infections whose causative agents are the organisms used in this study.